2001
DOI: 10.1016/s0923-2508(01)01241-4
|View full text |Cite
|
Sign up to set email alerts
|

Trends in the use of protozoa in the assessment of wastewater treatment

Abstract: Increasing environmental pollution and the continuous development of new chemicals and drugs has led to ever growing concern about the potential effects of these compounds directly or indirectly on human health. As concerns water pollution, protozoa seem to be an excellent tool to assess both toxicity and pollution: they are regarded as biological indicators of pollution when their presence or absence can be related to particular environmental conditions, and they are considered test organisms when a species o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
40
1
4

Year Published

2004
2004
2014
2014

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 79 publications
(46 citation statements)
references
References 40 publications
1
40
1
4
Order By: Relevance
“…Several studies on fungi and protozoa in activated sludge systems demonstrated that these eukaryotic organisms fulfil different tasks in wastewater systems, related to sludge dewaterability and toxic resistance, COD removal, nitrification or denitrification activities [28,29]. However in the present study they were only present when the fish processing wastewater was fed indicating their possible presence in the inoculum or in this kind of effluent.…”
Section: Inoculum and Wastewater Compositioncontrasting
confidence: 47%
“…Several studies on fungi and protozoa in activated sludge systems demonstrated that these eukaryotic organisms fulfil different tasks in wastewater systems, related to sludge dewaterability and toxic resistance, COD removal, nitrification or denitrification activities [28,29]. However in the present study they were only present when the fish processing wastewater was fed indicating their possible presence in the inoculum or in this kind of effluent.…”
Section: Inoculum and Wastewater Compositioncontrasting
confidence: 47%
“…It is accepted that the protozoan communities will be influenced in two pathways: to be manipulated directly by virtue of their inherent sensitivities to environment, and meanwhile to be modified indirectly in accordance with the potential changes of bacterial community structures through food chain (Curds and Cockburn, 1970;Zarda et al, 1998;Jezbera et al, 2005;Nicolau et al, 2005). For building the species-habitat relationship, most previous studies have been devoted to monitoring protozoan communities for predicting effluent quality and plant performance (Curds and Cockburn, 1970;Poole, 1984;Al-Shahwani and Horan, 1991;Salvadó et al, 1995;Martín-Cereceda et al, 1996).The species of protozoa present in activated sludge have been well inventoried as important bio-indicators since last century (Curds and Cockburn, 1970;Madoni and Ghetti, 1981;Madoni et al, 1993;Nicolau et al, 2001). Recently, with the awareness of their potential indications for operating conditions, some researchers have focused on evaluating the association of protozoan species with operational parameters (Esteban et al, 1991;Salvadó and Gracia, 1993;Salvadó , 1994;Martín-Cereceda et al, 1996;Lee et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Unlike water quality measurements, which only provide an instantaneous assessment of lake conditions, protozoa community can be used to identity past disturbances and toxic effects that are not readily detected by chemical means (Cairns and McCormick, 1993). Many studies have focused on the significance of protozoa in biological wastewater treatment Bharati et al, 2001;Nicolau et al, 2001;Scholz et al, 2002;wang et al, 2004;Lee et al, 2004;Madoni and Zangrossi, 2005).…”
Section: Introductionmentioning
confidence: 99%